Mengintegrasikan Crowdsourcing Dalam Bimbingan Konseling: Pendekatan Baru Untuk Mendapatkan Dukungan Komunitas: Integrating Crowdsourcing in Counseling Guidance: A New Approach to Getting Community - Amna, Syahraeni; Aswar, Aswar (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the potential of crowdsourcing as an innovative tool for integrating community support into guidance and counseling services. Crowdsourcing not only enables the collection of ideas and solutions from various stakeholders but also enriches the counseling experience by incorporating broader perspectives. By utilizing technology, this approach can enhance the accessibility and relevance of counseling services, especially in today’s digital era. However, despite its numerous advantages, the implementation of crowdsourcing in guidance and counseling still faces challenges, including the lack of technological infrastructure and limited awareness of its benefits among counselors and educational institutions. Collaborative and systematic efforts are needed to overcome these barriers so that guidance and counseling services can become more effective and responsive to students’ needs. Therefore, the integration of crowdsourcing presents a promising solution to improve the quality and effectiveness of counseling services by actively involving the community and creating a wider support network. This opens up opportunities for broader public participation in supporting mental health and individual well- being. The findings of this study contribute to the development of more inclusive, adaptive, and community-based counseling practices that align with the evolving demands of modern educational environments.